TACE Plus Lenvatinib Versus TACE Plus Sorafenib for Unresectable Hepatocellular Carcinoma With Portal Vein Tumor Thrombus: A Prospective Cohort Study - Yang, Biao; Jie, Luo; Yang, Ting; Chen, Mingyang; Gao, Yuemei; Zhang, Tian; Zhang, Yuzu; Wu, Hao; Liao, Zhengyin (Frontiers in Oncology, 2021)
Background and Objectives This study aimed to compare the efficacy of transarterial chemoembolization (TACE) plus sorafenib (TACE-S) to TACE plus lenvatinib (TACE-L) for the treatment of HCC with portal vein tumor thrombus (PVTT). Methods This cohort study recruited patients from September 2017 to September 2020. A total of 59 and 57 consecutive patients were treated with TACE-L and TACE-S, respectively. Results Before propensity score matching (PSM), comparing TACE-L to TACE-S, the median overall survival (OS) time was 16.4 months and 12.7 months, respectively [hazard ratio (HR) 1.34; 95% confidence interval (CI): 0.81-2.20; P = 0.25]. The median progression-free survival (PFS) time was 8.4 months and 7.43 months, respectively (HR 1.54; 95% CI: 0.98-2.41; P = 0.081). After PSM, the median OS time was 18.97 months and 10.77 months, respectively (HR 2.21; 95% CI: 1.12-4.38; P = 0.022); the median PFS time was 10.6 months (95% CI: 6.6-18.0 months) and 5.4 months (95% CI: 4.2-8.1 months), respectively (HR 2.62; 95% CI: 1.43-4.80; P = 0.002). After PSM, the overall response rate (ORR) was 66.8% vs. 33.3% [odds ratio (OR) 0.85; 1.05-6.90; P = 0.037]. Conclusion Both TACE-L and TACE-S are safe, well-tolerated treatments for HCC with PVTT. In HCC with PVTT, TACE-L was significantly superior to TACE-S with respect to OS, PFS, and ORR. Larger scale of randomized clinical trial is needed.